2013
DOI: 10.1002/ajmg.a.35965
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of two fetuses with deletions of 8p23.1, critical region for congenital diaphragmatic hernia and heart defects

Abstract: Microdeletions of 8p23.1 are mediated by low copy repeats and can cause congenital diaphragmatic hernia (CDH) and cardiac defects. Within this region, point mutations of the GATA4 gene have been shown to cause cardiac defects. However, the cause of CDH in these deletions has been difficult to determine due to the paucity of mutations that result in CDH, the lack of smaller deletions to refine the region and the reduced penetrance of CDH in these large deletions. Mice deficient for one copy of the Gata4 gene ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Emerging evidence has indicated that chromosomal abnormalities and genomic copy number variants (CNVs) are responsible for the pathogenesis of CHD . Numerical chromosomal abnormalities, such as trisomy 21, trisomy 18, and trisomy 13, and also rare causative CNVs at recurrent loci, such as 22q11, 8p23.1, and 1q21.1, have been associated with syndromic CHDs. Moreover, clear Mendelian inheritance for CHDs has been observed in a small proportion of patients with a positive family history for CHDs .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has indicated that chromosomal abnormalities and genomic copy number variants (CNVs) are responsible for the pathogenesis of CHD . Numerical chromosomal abnormalities, such as trisomy 21, trisomy 18, and trisomy 13, and also rare causative CNVs at recurrent loci, such as 22q11, 8p23.1, and 1q21.1, have been associated with syndromic CHDs. Moreover, clear Mendelian inheritance for CHDs has been observed in a small proportion of patients with a positive family history for CHDs .…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygous (AB) loci could not be identified. SNP microarray analysis was performed using the Affymetrix Cytoscan HD platform [17] which uses over 743,000 SNP probes and 1,953,000 NPCN probes with a median spacing of 0.88 kb. …”
Section: Clinical Characteristics Of the Patientmentioning
confidence: 99%
“…Duplications of some part of the olfactory receptor (OR) gene clusters serve as a source for the rearrangements of the short arm of chromosome 8 [Giglio et al, ; Buysse et al, ]. The 8p23.1 region and the GATA4 gene are “hotspots” for fetal heart development, as deletion and duplication of 8p23.1 are associated with heart defects including: atrial and/or ventricular septal defects, double outlet right ventricle, dextrocardia, pulmonary stenosis, and hypoplastic left heart syndrome [Pehlivan et al, ; Keitges et al, ]. Large deletions of 8p23.1 including the GATA4 gene are associated with more severe CHD than heterozygous GATA4 point mutations [Wat et al, ].…”
Section: Discussionmentioning
confidence: 99%